Political settlements and agricultural transformation in Africa : evidence for inclusive growth - Atela, Martin; Mustapha, Abdul Raufu (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores the ways in which political settlements can contribute to positive changes in Africa's agricultural and manufacturing sectors. Contemporary Africa has seen many governments, donors, and commercial private enterprises supporting innovative agricultural and agro-processing schemes with the purpose of diversifying economies. However, many of the schemes collapse or at best fail to generate the needed jobs. Focusing on case studies in Kenya, Nigeria and Ethiopia, this book takes an interdisciplinary approach that combines econometric modelling research, life histories, policy approaches methods, and political economy theory to reframe the field with new questions. The contributors offer alternative explanations for the failure of employment creation schemes in Africa and show how political settlements can bring together stakeholders to settle on win-win approaches to productive employment schemes and inclusive development. Providing new insights on the political economy of agrarian and labour relations in Africa, this book will be of interest to policy actors and development practitioners wishing to support inclusive growth in Africa, as well as to scholars of African politics and economics, public policy and development"--
Introduction and Overview / Abdul Raufu Mustapha, Kate Meagher and Nicholas Awortwi -- Political Economy and Settlements in Development and Employment Policies in Ethiopia / Assefa Admassie, Kassahun Berhanu Alemu and Mesfin Gebremichael -- Political Economy of Agriculture and Unemployment in Kenya / Paul Kamau, Winnie Mitullah, Joshua Kivuva and Martin Atela -- Political Settlements and the Rice and Cotton Industries in Nigeria / Aremu Fatai Ayinde, Kwaghe Patrick Vandi, Jijji Saadu, and Agbiboa Daniel Egiegba -- Inclusive Growth in the Wheat-Food Processing and Cotton-Textile Value Chains in Ethiopia / Assefa Admassie, Kassahun Berhanu Alemu, Mesfin Gebremichael and Martin Atela -- Employment Creation and Political Settlements in Kenya's Cut-Flower and Sugar Sub-Sectors / Winnie Mitullah, Paul Kamau and Joshua Kivuva -- Political Economy of Agriculture and Unemployment in Nigeria / Aremu Fatai Ayinde, Kwaghe Patrick Vandi, Jijji Saadu, and Agbiboa Daniel Egiegba.
Keywords: Agriculture and politics -- Africa; Agriculture -- Economic aspects -- Africa; Agricultural development projects -- Africa; BUSINESS & ECONOMICS -- Development -- Economic Development; SOCIAL SCIENCE -- Third World Development